Evaluation of anthelmintic activity of leaves of paederia foetida - YADU NANDAN DEY; MANAS KUMAR PAL (International Journal of Pharma and Bio Sciences, 2011)
Methanolic extract of the leaves of Paederia foetida were screened for its anthelmintic activity against Pheretima posthuma and Tubifex tubifex . The parameters like the time of paralysis and the time of death were determined by using the extract at the concentrations of 25,50 and 100 mg/ml. The extract exhibited significant anthelmintic activity at highest concentration of 100 mg/ml as compared with piperazine citrate (10 mg/ml) as standard reference and distilled water as control.